If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11=2+9(x-14)
We move all terms to the left:
11-(2+9(x-14))=0
We calculate terms in parentheses: -(2+9(x-14)), so:We get rid of parentheses
2+9(x-14)
determiningTheFunctionDomain 9(x-14)+2
We multiply parentheses
9x-126+2
We add all the numbers together, and all the variables
9x-124
Back to the equation:
-(9x-124)
-9x+124+11=0
We add all the numbers together, and all the variables
-9x+135=0
We move all terms containing x to the left, all other terms to the right
-9x=-135
x=-135/-9
x=+15
| 2a-2+3=-2+8a | | 0.25(40)+0.6x=0.3(40+x) | | 7=-x62-4x | | -5=b-7/5 | | -7.1j=-11.3j+0.84 | | -1.05x9.2=-9.7 | | (31+9)^2=x | | X+12=1.5(x-3) | | 112+7x=22 | | 112+7x=220 | | -13.7v−4.53=-11.7v+13.67 | | -5n+34=-2-14n | | x=2293+0.67(576.6) | | 73,142-n=81,607 | | x/5-6=3/5 | | 2(3x-1)+5x=14x-7 | | 2x^2+62x-720=0 | | 3^2x-5+7=10 | | 81,607-n=73,142 | | x-0.2x+12=24 | | -9j+9=9-9j | | 2(5x+25)=10x+25 | | 73,142=81,607-n | | 3-5z=-5z-9 | | x=2293-0.99(576.6) | | x+6(3+5)=x+6(4+4) | | -4+4h=4h-4 | | 10x-4=2(5x+2) | | 5(2c+7)-3c=8 | | -7m+3=-3-9m | | 5x+2=7x–7 | | -2h+18−5=-20+9h |